Meta Analisis: Hubungan Pendidikan Ibu dan Jenis Persalinan dengan Inisiasi Menyusui Dini (IMD) - Rosihan Adhani; Achmad Rofi'i; Eka Maya Putri (HB PRESS, 2021)
One of the factors that play an important role in improving human quality is the provision of breast milk as early as possible after the child is born, known as early initiation of breastfeeding (EIB).This study aimed to determine the tendency of a greater relationship between mother's education and type of delivery with EIB.This was a meta-analysis study. The data were collected by searching online journals, using the PubMed and Google Scholar databases. The research protocol in meta-analysis can use the concept of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Journal identification is done using the Critical Appraisal Skills Program (CAPS) table and data synthesis using the SPIDER format (Sample, Phenomenon of Interest, Design, Evaluation and Research type). Synthesis of results using a meta-analysis technique (forest plot) using the statistical application Comprehensive Meta Analysis Version 3. The results showed that the mother’s education had an I² value of 88% and a p-value of heterogeneity test of <0,05, meaning that the heterogeneity between studies was high. Random Effect Model produced a combined effect size value of 1,171 (95% CI: 0,912-1,504) with a z-value of 1,237 and a p-value of 0,216. Type of delivery had an I² value of 95% and a p-value of the heterogeneity test of <0,05, meaning that the heterogeneity between studies was high.The Random Effect Model produced an effect size value of 0,588 (95% CI: 0,364-0,950) with a significant z-value of -2,172 and a p-value of 0,030.The results of the combined articles showed that the relationship between mother's education and EIB had a p-value of 0,216 and OR of 1,17. Nine articles about type of delivery showed were obtained with the result that there was no trend of relationship between this variable and EIB. The combined results showed that the relationship between the type of delivery and early initiation of breastfeeding had a p-value of 0,030 and OR of 0,588.